Development and validation of a new spectrophotometric method for the determination of gabapentin in capsules - Miedviedieva, K. P.; Vasyuk, S. O.; Portna, O. O.; Мєдвєдєва, Катерина Павлівна; Васюк, Світлана Олександрівна; Портна, Олена Олексіївна (My University, 2023)
In Ukraine, there are about 100 thousand people with epilepsy. Gabapentin is an effective antiepileptic agent for oral use, presented in capsules of different dosages from different manufacturers. Therefore, the urgent task of pharmaceutical analysis today is the development of highly accurate, reliable, affordable and fast methods of quantitative determination. The aim of the work is to develop a spectrophotometric technique for the quantitative determination of gabapentin in capsules based on the reaction with diazole red 2J in compliance with the SPhU. Material and methods. As reagent and solvent, diazole red 2J of AR grade, acetone of AR grade and purified water was used. Analytical equipment: Specord 200 and Specord 250 Plus spectrophotometers, ABT-120-5DM and Radwag XA 210.4Y electronic scales, Elmasonic E 60H and Sonorex Digitec DT100H ultrasonic baths, measuring glassware of A class. Results. A simple, accurate and eco-friendly colourimetric method was developed for the quantification of gabapentin in capsules. The method was based on the reaction of gabapentin with diazole red 2J to give a coloured product having analytical maxima at 390 nm. Factors affecting colour development and stability were optimized and incorporated into the procedure. Regression analysis of Beer’s plot showed a good correlation (not less than 0.999) in a concentration range of 2.10–3.64 mg/100 ml. The detection and quantification limits were 2.25 % and 6.19 %, respectively. The intra- and inter-laboratory precision demonstrates and reflects no interference by the capsule additives and confirms the reproducibility of the method in the selected concentration range. The prediction of the total uncertainty of the results of the developed method is calculated and displayed to assess the correctness of the reproduction of the method. Conclusions. It has been proven that the developed method meets the requirements of the State Pharmacopoeia of Ukraine and allows to perform the correct quality control of medicinal products
Keywords: spectrophotometry; gabapentin; diazole red 2J; validation studies; SPhU